Izbrana poglavja iz zgodovine selitev od začetkov do danes - Klemenčič, Matjaž; Maver, Aleš; Žiberna, Igor; Drole, Zmago (University of Maribor Press, 2017)
Selected Chapters of the History of Migration from the Beginnings to the Present. The main aim of the present volume was to give a concise outline of the main migratory processes through the human history. The text is divided in two main parts. The first one is dedicated to main lines of global migration from the prehistory till today. The second, shorter one is centred around Slovenia as both target of migration and as a traditional land of emmigration. In first chapters of the first part, some key notions, used in the book, are discussed. In later chapters, material is organized mainly using the chronological framework. The lasting influence of these migratory processes on the present-day linguistic map of the world was surely reason enough to include a longer discussion of migration of the early speakers of Indo-European around the globe. The discussion of great migratory waves in late antiquity and in the early middle ages is one of the core chapters of the book, since the influence of these processes on the present-day Europe can still harldly be overeastimated. The development in some main immigration countries and regions is debated separately from the early 19th century on. Thereby, the USA, Canada, Australia, Latin America and Western Europe are identified as main points of interest. Not only origin of immigrants and causes of their immigration, but also emerging immigration policies of the host countries are thoroughly analyzed. This pattern then continues to the end of the first part. The chronological framework is breeched to some degree in order to emphasize the particular importance of developments connected to the World War II and its aftermath. The last chapter of the first part, dedicated to the recent developments, understandably centres around two core processes, around migratory movements caused by political and economic opening manywhere in the world after 1989, as well around recent migration crisis starting around the middle of the 2010s. The second, shorter part of the book is organized quite differently. The chronological framework gives way to the discussion of the role of Slovenian historical lands in migratory processes through the ages.